User talk:PaoloMartini

From HaskellWiki
Revision as of 20:14, 15 September 2006 by PaoloMartini (talk | contribs)
Jump to: navigation, search

p(x) = \sum_{i=0}^n a_i x^i, a_n \neq 0

p(x) = a_n x^n + \sum_{i=0}^{n-1} a_i x^i

p(x-1) = a_n (x-1)^n + \sum_{i=0}^{n-1} a_i (x-1)^i

(x-1)^n = \sum_{k=0}^n {n \choose k} x^{n-k} (-1)^k

p(x-1) = a_n \sum_{k=0}^n {n \choose k} x^{n-k} (-1)^k + \sum_{i=0}^{n-1} a_i (x-1)^i

p(x-1) = a_n x^n + a_n \sum_{k=1}^n {n \choose k} x^{n-k} (-1)^k + \sum_{i=0}^{n-1} a_i (x-1)^i